Isolation of cDNA clones specific for collagen IV and laminin from mouse teratocarcinoma cells. - Wang, S Y (1983)
The synthesis of the proteins laminin and collagen IV is stimulated approximately equal to 20-fold in F9 mouse teratocarcinoma stem cells after treatment of the cells with retinoic acid and N6, O2'-dibutyryl-cAMP (Bt2cAMP). A cDNA library from F9 cells treated with retinoic acid, Bt2cAMP, and theophylline (F9-R + DBC cells) was constructed to isolate cDNA coding for collagen IV or laminin. The recombinant plasmids were screened by differential colony hybridization to cDNA synthesized from poly(A)+ RNA isolated from F9 stem and F9-R + DBC cells. Differentially hybridizing plasmids were then used as probes to hybridize to RNA transfer blots to determine the size of their specific mRNA. Only plasmids containing cDNA sequences specific for high molecular weight mRNA were further analyzed. Studies by hybridization-selection, in vitro translation, and immunoprecipitation showed that a plasmid clone, pc15, contains cDNA homologous to collagen IV (alpha 2) mRNA, and another plasmid clone, pc156, contains cDNA homologous to laminin B mRNA. By RNA blot analyses, the size of mRNA coding for collagen IV (alpha 2) is 7.6 kilobases; the size of mRNA for laminin is 6.8 kilobases. Using the technique of RNA blot hybridization, we studied the time course of the increase in mRNA coding for collagen IV (alpha 2) and laminin B in F9 cells after retinoic acid and Bt2cAMP treatment. Both collagen IV (alpha 2) and laminin B mRNAs are present in F9 stem cells. Collagen IV (alpha 2) mRNA and laminin B mRNA levels increase slightly at approximately 12 hr after retinoic acid and Bt2cAMP addition, with a dramatic increase between 12 and 24 hr after drug treatment.